ANALYSIS OF CAROTENOIDS IN SWEET POTATOES USING HPLC TO HELP COMBAT VITAMIN A DEFICIENCY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The fascinating and diverse family of organic compounds called carotenoids is widely found in plants, as well as some bacteria and algae. These natural pigments, with vibrant colours ranging from bright yellow to deep red and flamboyant red, attract attention for their importance in plant biology and their effect on human health. One of the most common vitamin deficiencies in the world is vitamin A deficiency.The name carotenoids come from the vegetable carrot (carrot in Latin), where there are many well-known beta-carotenoids. These compounds are essential to biological processes beyond contributing to nature's variety of colours.A deficiency, a persistent public health problem in many parts of the world. The precise quantification of carotenoids, in particular beta-carotene, makes it possible to evaluate the specific contribution of these sweet potatoes to the intake of vitamin A in the diet.This study offers important data that could guide efforts to promote sweet potato consumption, particularly in regions where vitamin A deficiency is a concern. These tubers can be strategically included in diets to improve the availability of vitamin A, helping to mitigate the risks associated with this nutritional deficiency.In sum, this HPLC analysis of carotenoids in sweet potatoes provides a solid basis for the promotion of these tubers as a dietary resource rich in provitamin A, thereby contributing to the fight against vitamin A deficiency and the promotion of health. in the communities concerned.